2015
DOI: 10.1055/s-0035-1558095
|View full text |Cite|
|
Sign up to set email alerts
|

Lavandula angustifolia and Lavandula latifolia Essential Oils from Spain: Aromatic Profile and Bioactivities

Abstract: Compositions of true lavender (Lavandula angustifolia) and spike lavender (Lavandula latifolia) essential oils, cultivated and extracted in the Southeast of Spain, were determined by gas chromatography coupled with mass spectrometry detection, obtaining both relative (peak area) and absolute (using standard curves) concentrations. Linalool (37-54 %), linalyl acetate (21-36 %) and (E)-β-caryophyllene (1-3 %) were the most abundant components for L. angustifolia. Linalool (35-51 %), eucalyptol (26-32 %), camphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 35 publications
2
40
0
1
Order By: Relevance
“…There is relatively little information dealing with the antioxidant properties of LO. Biochemical analysis (2.2-diphenyl-1-picrylhydrazyl -DPPH and 2.2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)-ABTS assays) and our preliminary results suggest that LO may display antioxidant activity [51]. Cadet and Douki [52] found out that in in vitro experiments LO inhibited the production of singlet oxygen ( 1 O 2 ), the main photoproduct of UVA.…”
Section: Discussionmentioning
confidence: 60%
“…There is relatively little information dealing with the antioxidant properties of LO. Biochemical analysis (2.2-diphenyl-1-picrylhydrazyl -DPPH and 2.2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)-ABTS assays) and our preliminary results suggest that LO may display antioxidant activity [51]. Cadet and Douki [52] found out that in in vitro experiments LO inhibited the production of singlet oxygen ( 1 O 2 ), the main photoproduct of UVA.…”
Section: Discussionmentioning
confidence: 60%
“…Among studies on L. angustifolia, a recent work of Smigielski et al [43] compares fresh and dried plant material finding no significant differences in terms of chemical composition of essential oils but rather a higher antioxidant activity in the oil from fresh aerial parts. Recent works [35,37,41,42] report a linalool predominance in L. angustifolia essential oils from Croatia, Italy, Turkey and Spain respectively. Kivrak and Singh et al, [38,40] report two cases of linalyl acetate chemotypes from Turkey and India respectively, while Kabouche et al, [39] reports 1,8-cineole chemotype in Algerian populations.…”
Section: Lavendermentioning
confidence: 99%
“…Among the herbs belonging to the Lamiaceae family, rosemary (Rosmarinus officinalis L.) is by far the one to which the highest number of biological activities have been ascribed. In the latest five years, the in-vivo hepato-and hepato-renal protective effects of rosemary have been extensively studied; as example Hegazy et al [426] investigated the preventive effect of the aqueous extract of this herb on the gentamicininduced hepatotoxicity in rats with promising result connecting these activities with the presence in the extract of catechin (37), coumarin (38), cinnamic acid (39), rutin (40), sinapic acid (41) and oleuropein (42), whilst Mohamed et al [427] studied the protection of rosemary ethanolic extract on lead acetate hepatoand nephrotoxicity in male albino rabbits. The authors found that pre-treatment with rosemary extract significantly suppressed levels of hepatic and renal damage products as well as lipid peroxidation.…”
Section: Rosemarymentioning
confidence: 99%
“…As described in the literature, the essential oil of this plant is mostly composed by oxygen-containing monoterpenes compounds [17]. Although the composition of the essential oil of Lavandula angustifolia shows a remarkable variability, depending on the source, the season or the method of isolation [18][19][20][21][22], the main constituents are predominantly linalool, 1,8-cineole or linalyl acetate, and oxygenated monoterpenes constitute, largely, the major group. A recent publication showed that the essential oil of Lavender and its main constituent, linalool, have a potential inhibitory effect on neuronal spontaneous electrical activity, using rat neuronal networks [20].…”
Section: Discussionmentioning
confidence: 99%